Strategies and Challenges in Teaching Speaking by English Tutors: A Study in Madani Super Camp English Classes - Sukmojati, Edi; Ribahan, Ribahan; Rahmat, Hery (Universitas Siliwangi, 2023)
Speaking is an important skill needed in communication and requires good training as well as professional and experienced English tutors. The speaking tutors will encounter various difficulties and need to employ effective teaching strategies to overcome them. This study aimed to find out the types of challenges faced by the English tutors in the Madani Super Camp (MSC) Course Narmada in teaching speaking and the types of learning strategies applied by the tutors to overcome the challenges in teaching speaking. This qualitative descriptive research involved eight English teachers in the MSC Course Narmada as respondents. The data were obtained by using closed-ended questions and semi-structured interviews, which were transcribed descriptively. In addition, the data analysis used is data reduction, data display, and conclusion drawing. The results of the research showed that the tutors faced five challenges in teaching English, including a lack of student discipline, additional work, a lack of self-confidence, a lack of technical teaching, and controlling the classroom and class management. The researcher reveals the research findings related to the learning strategies applied by the tutors to overcome the challenges in teaching speaking ability, including discussion and classroom interaction, storytelling, classroom practice, games, and picture descriptions. Keywords: Tutors’ Challenges; Tutors’ Strategies; Teaching Speaking.